2019
DOI: 10.1523/jneurosci.0578-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal Dysfunction in Down Syndrome Is APP-Dependent and Mediated by APP-βCTF (C99)

Abstract: Lysosomal failure underlies pathogenesis of numerous congenital neurodegenerative disorders and is an early and progressive feature of Alzheimer's disease (AD) pathogenesis. Here, we report that lysosomal dysfunction in Down ayndrome (trisomy 21), a neurodevelopmental disorder and form of early onset AD, requires the extra gene copy of amyloid precursor protein (APP) and is specifically mediated by the ␤ cleaved carboxy terminal fragment of APP (APP-␤CTF, C99). In primary fibroblasts from individuals with DS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
141
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(155 citation statements)
references
References 112 publications
(159 reference statements)
14
141
0
Order By: Relevance
“…The deleterious effects of this on the brains of mice (defective mitochondrial biogenesis and function and stimulation of inflammatory responses) could be alleviated by increasing the levels of iron in their diet. The observations of Nixon and colleagues that acidification of the endolysomal pathway is affected both by fAD mutations in PSEN1 [46] and excessive dosage of the APP gene [54], together with our observations from our fAD-like psen1 Q96_K97del /+ mutant zebrafish, support the possibility that fAD brains may suffer a ferrous iron deficiency in a background of ferric iron overload. Intriguingly, the greatest genetic risk factor for late onset AD, the e4 allele of the gene APOE, appears to increase lysosomal pH [55] but e4's increased risk of AD is alleviated in individuals who possess the HFE 282Y allele that predisposes to the iron overload disease hemochromatosis [56].…”
Section: Discussionsupporting
confidence: 80%
“…The deleterious effects of this on the brains of mice (defective mitochondrial biogenesis and function and stimulation of inflammatory responses) could be alleviated by increasing the levels of iron in their diet. The observations of Nixon and colleagues that acidification of the endolysomal pathway is affected both by fAD mutations in PSEN1 [46] and excessive dosage of the APP gene [54], together with our observations from our fAD-like psen1 Q96_K97del /+ mutant zebrafish, support the possibility that fAD brains may suffer a ferrous iron deficiency in a background of ferric iron overload. Intriguingly, the greatest genetic risk factor for late onset AD, the e4 allele of the gene APOE, appears to increase lysosomal pH [55] but e4's increased risk of AD is alleviated in individuals who possess the HFE 282Y allele that predisposes to the iron overload disease hemochromatosis [56].…”
Section: Discussionsupporting
confidence: 80%
“…(We suggested that the involvement of PRESENILIN holoproteins in multimerization may explain the “reading frame preservation” rule that states that all EOfAD mutations in the PSEN genes must preserve an open reading frame that uses the original stop codon (12). ) Curiously, both of the PRESENILIN activities mentioned above, the regulation of MAM formation and of endolysosomal acidification, appear to be mediated by the C99 fragment (β-CTF) of APP (57, 60) and this implies that these activities of the PRESENILINs may share a common molecular mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Lysosomal hydrolase (e.g., cathepsin) activity and proteolysis indeed require optimal acidic pH [133]. In AD, presenilin-1 mutations and elevated CTFβ peptide levels impair lysosomal acidification and cathepsin activity, causing a massive pileup of autophagic vesicles with undigested autophagy substrates in neurons [134,135]. Presenilin-1 functional loss due to its mutation impairs the V-ATPase function, which leads to altered lysosomal Ca 2+ homeostasis and results in defective lysosomal acidification and cathepsin D activity [136].…”
Section: Lysosomes Functional Restoration With Nanotechnologymentioning
confidence: 99%
“…Presenilin-1 functional loss due to its mutation impairs the V-ATPase function, which leads to altered lysosomal Ca 2+ homeostasis and results in defective lysosomal acidification and cathepsin D activity [136]. Also, amyloidogenic APP cleavage product CTFβ shifts lysosomal pH towards alkalinity and reduce cathepsin D activity [135]. These lysosome-related AD pathogenic events can be prevented with acidic nanoparticles.…”
Section: Lysosomes Functional Restoration With Nanotechnologymentioning
confidence: 99%